Penggunaan Klausa Relatif Pada Pembelajar BIPA di Unit Pelaksana Teknis (UPT) Bahasa Universitas Sebelas Maret Surakarta - Anggun Melati Sari; Andayani Andayani; Sumarlam Sumarlam (Unipdu Jombang, 2017)
AbstractThis study aimed to describe the use of relative clauses Indonesian learners for Foreign Speakers (BIPA) grade-level academic scholarship at the Technical Implementation Unit (UPT) Language of Sebelas Maret University. The subject matter is the form of the use of relative clauses and the types of errors in relative clause. The data used in this study is the form of oral’s data and writing’s data. The data derived from the oral-speech BIPA’s learners in which there is relative clause while the writing’s data derived from the sentences in BIPA learner’s essay in which there is relative clause. The data were analyzed using agih methods and advanced technique of agih methods. The results of this study indicate that the use of relative clauses in BIPA learners using the perelative words “yang”. Acquisition of the relative clauses that relativize the thermic elements and errors in the relative clause that removes the noun element occupying the highest level as well as describe the highest degree of mastery in relative clauses. This study concluded that the form of the use of relative clause also describe the mastery level of difficulty of each type of relative clause learners BIPA.Keywords: clause, relative clause, Indonesian for foreign speakers (BIPA)